The Impact of Sex Differences on Renal Protective Effects of Lipopolysaccharide Preconditioning in Septic Shock - Mehri Kadkhodaee; Behjat Seifi; Mina Ranjbaran; Sedigheh Shams; Fatemeh Delavari; Atefeh Najafi; Zahra Sedaghat; Hossein Khastar (Iranian Journal of Medical Sciences, 2020)
Background: Induction of septic shock by lipopolysaccharide (LPS) may lead to acute renal failure. The present study aimed to investigate the impact of sex differences on the effectiveness of low-dose LPS preconditioning (LPS-PC) on LPS-induced acute renal failure in rats. Methods: This study was conducted at Tehran University of Medical Sciences, in 2017. A total of 48 Wistar rats were equally divided into two groups of male and female rats. The rats in each group were then allocated to three groups (n=8 per group), namely control, septic shock, and LPS-PC group. A high dose of LPS was administered for septic shock induction. LPS-PC was induced by injecting LPS before sepsis induction. The effect of sex differences on renal functional indices, renal oxidative stress markers, plasma tumor necrosis factor-α level, and renal histological changes was evaluated. Data were analyzed using two-way ANOVA followed by Tukey’s post hoc test. Results: In the septic shock groups, renal functional parameters (creatinine [Cr] and blood urea nitrogen [BUN]) were increased in both sexes. However, the increase was more significant in male rats (male rats: Cr=2.14±0.13, BUN=81±4.15; female rats: Cr=1.64±0.12, BUN=50±2.7). LPS-PC reduced these indices in both sexes (male rats: Cr=1.24±0.03, BUN=57±4.1; female rats: Cr=0.86±0.02, BUN=30.31±2.25). Renal superoxide dismutase (SOD) activity (male rats: 11.54±1.34, female rats: 24.4±2.04) and catalase (CAT) activity (male rats: 15±1.74, female rats: 25.75±1.97) were significantly higher in the female septic group. LPS-PC significantly increased SOD (male rats: 25.7±2.45, female rats: 42.6±3.31) and CAT (male rats: 37.25±2.34, female rats: 59.21±3.29) activities in renal tissue samples in the LPS-PC group in both sexes compared to the septic groups. In the LPS groups, plasma tumor necrosis factor-α (male rats: 375±25.65, female rats: 285.45±25.94) were significantly higher than in the LPS-PC groups (male rats: 250±21.35, female rats: 121±24.14). Conclusion: Male rats were more susceptible to sepsis-induced renal damage. LPS-PC had protective effects on the LPS-induced renal injury, and these effects were most prominent in female rats.